Forest Attendance in the Times of COVID-19-A Case Study on the Example of the Czech Republic - Jarský, Vilém; Palátová, Petra; Riedl, Marcel; Zahradník, Daniel; Rinn, Radek; Hochmalová, Miroslava (International journal of environmental research and public health, 2022)
The COVID-19 pandemic affected people all over the world, including the Czech Republic (CZ). In the CZ, a number of measures were applied in 2020 to reduce the contact between people and their mobility. This article dealt with the importance of forests during the pandemic. Data from 2019 and 2020 were compared. The qualitative data were obtained from two nationwide surveys, the first focused on forest attendance and forest fruit collection (about 1000 respondents per year), the second on the motivation to visit the forests (about 3700 respondents per year). The quantitative data were obtained on the regional level by analysing data from mobility counters. The impact of government restrictions was assessed. Findings: (1) there was a significant increase in the number of people who frequently visited the forest in 2020; (2) in 2020, the amount of households that collected forest fruits increased and was the highest for the monitored period; (3) the increased forest attendance significantly corresponded to the government restrictions. The analysis confirmed the great importance of forests for the citizens and, at the same time, the increased pressure on the forests' use-forest attendance and forest crops picking-(especially suburban ones) in times of COVID-19 restrictions.
Keywords: payments for ecosystem services; lesy; stromy; COVID-19 pandemic; pandemie; COVID-19; Pandemics; Trees; Humans; Česká republika; SARS-CoV-2; zachování přírodních zdrojů; lidé; forest attendance; government restrictions; Forests; Conservation of Natural Resources; Czech Republic